Prediction of PbLi fluid flow and temperature field in a thermal convection loop for qualification of fusion materials. (June 2021) - Jiang, Y.; Smolentsev, S.; Jun, J.; Pint, B.; Kessel, C.
Highlights: The PbLi flow in the TCL is turbulent and about fully developed over the major length of the hot and cold leg; The most significant changes in the flow occur in the corner regions where Dean vortices are observed; Samples inside the loop cause flow obstruction resulting in lower velocities, higher maximum and lower minimum temperatures; A permanent magnet as a part of the electromagnetic flow meter significantly reduces the circulation velocity by a factor of 2-3; Changes of the surface emissivity in the course of the experimental studies can cause significant variance of the loop temperature. Abstract: Two modeling tools, a thermohydraulics code and a computational model in COMSOL Multiphysics, have been developed, tested and then applied to the analysis of fluid flow and heat transfer in a thermal convection loop (TCL). Such a device has recently been used to experimentally evaluate corrosion compatibility of APMT (Fe–21Cr–5Al–3Mo) steel with high-temperature molten eutectic lead-lithium (PbLi) alloy at Oak Ridge National Lab, TN, USA. The 1-D thermohydraulics code allows for rapid calculations of the loop parameters as a function of the applied heat flux. The supplemental COMSOL finite-element computations provide detailed 3-D velocity and temperature field data but are much more time consuming. Both modelling tools demonstrate an excellent agreement in the computed circulation velocity as well as maximum and minimum temperatures. The performed TCL analysis focuses on flow development in the "hot" and "cold" legs, formation of Dean vortices in corner regions, blocking effect of the immersed samples, and radiative and convective cooling effects under the experiment-relevant conditions for Prandtl number Pr =0.015, Grashof numbers G r ∼ 10 7, and Reynolds numbers R e ∼ 10 4 .